Protein glycosylation in pmt mutants of Saccharomyces cerevisiae. Influence of heterologously expressed cellobiohydrolase II of Trichoderma reesei and elevated levels of GDP-mannose and cis-prenyltransferase activity - Górka-Nieć, Wioletta; Bańkowska, Renata; Palamarczyk, Grażyna; Krotkiewski, Hubert; Kruszewska, Joanna S. (Biochimica et biophysica acta, 2007)
Protein O-mannosylation has been postulated to be critical for production and secretion of glycoproteins in fungi. Therefore, understanding the regulation of this process and the influence of heterologous expression of glycoproteins on the activity of enzymes engaged in O-glycosylation are of considerable interest. In this study we expressed cellobiohydrolase II (CBHII) of T. reesei, which is normally highly O-mannosylated, in Saccharomyces cerevisiae pmt mutants partially blocked in O-mannosylation. We found that the lack of Pmt1 or Pmt2 protein O-mannosyltransferase activity limited the glycosylation of CBHII, but it did not affect its secretion. The S. cerevisiae pmt1Δ and pmt2Δ mutants expressing T. reesei cbh2 gene showed a decrease of GDP-mannose level and a very high activity of cis-prenyltransferase compared to untransformed strains. On the other hand, elevation of cis-prenyltransferase activity by overexpression of the S. cerevisiae RER2 gene in these mutants led to an increase of dolichyl phosphate mannose synthase activity, but it did not influence the activity of O-mannosyltransferases. Overexpression of the MPG1 gene increased the level of GDP-mannose and stimulated the activity of mannosyltransferases elongating O-linked sugar chains, leading to partial restoration of CBHII glycosylation.